Temperature-dependent electrosynthesis of PEDOT:PSS: enhanced Na+ transfer targeting high-performance Na-ion batteries - Santos, Daniel R.; Zeferino, Jorge F.; Viana, Ana S.; Wijayantha, Upul K. G.; Lobato, Killian; Correia, Jorge P. (Elsevier, 2025)
Poly(3,4-ethylenedioxythiophene):Poly(sodium 4-styrenesulfonate) (PEDOT:PSS) is a versatile conducting polymer with physicochemical properties favourable for energy storage applications, such as chemical and mechanic stability and flexibility. However, the temperature at which the polymer is synthesised can significantly influence its properties. In this study, a detailed investigation of the effect of temperature on the electroactivity, morphology, optical properties, and ionic/solvent transport during the redox conversion of potentiostatically and galvanostatically synthesised films was conducted. Electrochemical data, supported by ellipsometry, atomic force microscopy, microgravimetry, and probe beam deflection measurements, revealed that films synthesised at lower temperatures (0 °C) were more compact compared to those synthesised at higher temperatures (40 °C). Films synthesised at 0 °C also exhibited near-ideal reversibility, with a QO/QR ratio of ca. 1. Importantly, the 0 °C films showed a strong pseudocationic doping behaviour, characterised by predominant sodium ion exchange during redox processes. In contrast, films synthesised at 40 °C exhibited mixed ion participation (both sodium and perchlorate), which could negatively impact the performance of electrode material in battery applications. This study demonstrates the potential of PEDOT:PSS as a versatile material for sodium ion cathodes, with properties that can be finely tuned through the synthesis temperature, yielding more compact ion-storage films at lower temperatures.
Keywords: PEDOT:PSS; Temperature-dependent electrosynthesis; Pseudocationic doping; Na-ion exchange polymer; 3403 Macromolecular and Materials Chemistry; 34 Chemical Sciences; 3406 Physical Chemistry; 40 Engineering; 4016 Materials Engineering; Energy; 51 Physical sciences